The Tsetse Metabolic Gambit: Living on Blood by Relying on Symbionts Demands Synchronization - Lee, Mason H.; Medina Munoz, Miguel; Rio, Rita V. M. (Frontiers in Microbiology, 2022)
Tsetse flies have socioeconomic significance as the obligate vector of multiple Trypanosoma parasites, the causative agents of Human and Animal African Trypanosomiases. Like many animals subsisting on a limited diet, microbial symbiosis is key to supplementing nutrient deficiencies necessary for metabolic, reproductive and immune functions. Extensive studies on the microbiota in parallel to tsetse biology have unraveled the many dependencies partners have for one another. But far less is known mechanistically on how products are swapped between partners and how these metabolic exchanges are regulated, especially to address changing physiological needs. More specifically, how do metabolites contributed by one partner get to the right place at the right time and in the right amounts to the other partner? Epigenetics is the study of molecules and mechanisms that regulate the inheritance, gene activity and expression of traits that are not due to DNA sequence alone. The roles that epigenetics provide as a mechanistic link between host phenotype, metabolism and microbiota (both in composition and activity) is relatively unknown and represents a frontier of exploration. Here, we take a closer look at blood feeding insects with emphasis on the tsetse fly, to specifically propose roles for microRNAs (miRNA) and DNA methylation, in maintaining insect-microbiota functional homeostasis. We provide empirical details to addressing these hypotheses and advancing these studies. Deciphering how microbiota and host activity are harmonized may foster multiple applications towards manipulating host health, including identifying novel targets for innovative vector control strategies to counter insidious pests such as tsetse.